The impact of living and working longer on pension income in five European countries: Estonia, Finland, Hungary, the Netherlands and Poland - Elena Jarocinska; Anna Ruzik; Theo Nijman; Andres V\~ork; Niku Määttänen; Robert Gál (Center for Social and Economic Research (CASE), 2014)
Life expectancies are rapidly increasing and uncertain in all countries in Europe. To keep pension systems affordable, policy reforms are to be implemented which will encourage individuals to work longer. In this paper we analyze the impact of working and living longer on pension incomes in five European countries and assess the impact of these policy reforms on the financial well-being of the elderly. The paper shows the diversity of the policy measures taken in these countries. Furthermore, we analyze the financial incentives for working longer and postponing claiming pension benefits and we assess the attractiveness of these options. Lastly, we study how increases in life expectancies and survival probabilities affect pension incomes.
Keywords: H55; J11; J26; 330; pension benefits; life expectancy; retirement age; policy reforms